2020
DOI: 10.1097/jcma.0000000000000463
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestation and disease progression in COVID-19 infection

Abstract: Coronavirus disease 2019 (COVID-19) is mainly an infectious disease of the respiratory system transmitted through air droplets, and pulmonary symptoms constitute main presentations of this disease. However, COVID-19 demonstrates a clinically diverse manifestation ranging from asymptomatic presentation to critically illness with severe pneumonia, acute respiratory distress syndrome, respiratory failure, or multiple organ failure. Accumulating evidences demonstrated that COVID-19 has extrapulmonary involvement, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
123
1
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(163 citation statements)
references
References 88 publications
7
123
1
6
Order By: Relevance
“…Our study revealed an overall mortality of 32.4% (22/68 patients; 3 missing) in COVID-19 patients who had developed DKA, DKA/HHS, and HHS. Interestingly, two recently published case series, whose data are not included in the present study as they are not presented analytically, report mortality rates that range from as low as 7.7% (2/26 patients) [12] and 1/7 patients (12.9%) [71], to 50% (25/50 patients) [19]; however, these case series derive from a single centers and thus might not be representative.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Our study revealed an overall mortality of 32.4% (22/68 patients; 3 missing) in COVID-19 patients who had developed DKA, DKA/HHS, and HHS. Interestingly, two recently published case series, whose data are not included in the present study as they are not presented analytically, report mortality rates that range from as low as 7.7% (2/26 patients) [12] and 1/7 patients (12.9%) [71], to 50% (25/50 patients) [19]; however, these case series derive from a single centers and thus might not be representative.…”
Section: Discussionmentioning
confidence: 90%
“…presenting with DKA and long-lasting ketosis [12,13]. Diabetic ketoacidosis was the most common reason for hospitalization of T1D patients with COVID-19 [6] [14].…”
Section: Covid-19 Is Associated With Hyperglycaemic Emergencies With mentioning
confidence: 99%
See 1 more Smart Citation
“…COVID-19 is associated with hyperglycaemic emergencies with overrepresentation of T2D in patients presenting with DKA and long-lasting ketosis [13,14]. DKA was the most common reason for hospitalization of T1D patients with COVID-19 [6,15].…”
Section: Introductionmentioning
confidence: 99%
“…The underlying pathophysiology of COVID-19 and DM intertwining has not been totally explained; however, diabetes patients have an increased risk of infection and acute respiratory distress syndrome compared with the general population [2] [3] [4] [5] [6], while direct cytopathic effects of SARS-CoV-2 on pancreatic b-cell populations have been proposed [7]. COVID-19 is associated with hyperglycaemic emergencies as diabetic ketoacidosis (DKA), hyperglycaemic hyperosmolar State (HHS), euglycaemic diabetic ketoacidosis (EDKA), and combined DKA/HHS [8] [9]. The over-activity of immune system might further explain COVID-19-related severe and resistant to conventional therapy DKA episodes [10].…”
Section: Text Introductionmentioning
confidence: 99%